Sharaz-de : tales from the Arabian nights - Toppi, Sergio; Gauvin, Edward (Los Angeles, Calif. : Archaia, 2012)
A set of tales inspired by the "Arabian Nights" by European comics master Sergio Toppi, exploring a barbaric society where the supernatural is the only remedy to injustice, as Sharaz-de, captive to a cruel and despotic king, must each night spin tales to entertain her master and save her head from the executioner. Tales filled with evil spirits, treasures, risk, and danger, but always at their center the passions of gods and men.
"Originally published in France by MOSQUITO, 2005"--T.p. verso.
Originally presented in Italian.
Translated from the Italian by Edward Gauvin.
Keywords: Arabian nights -- Comic books, strips, etc; Arabian Peninsula -- Comic books, strips, etc